Lifelines : the resilient infrastructure opportunity - Hallegatte, Stéphane; Rentschler, Jun; Rozenberg, Julie (Sustainable infrastructure series., 2019)
"This report lays out a framework for understanding infrastructure resilience - the ability of infrastructure systems to function and meet users' needs during and after a natural hazard"--